Branchial cleft cyst arising in posterior mediastinum: A case report - Li, Lin-Jie; Han, Zhi-Feng; Shang, Sheng-Tao (Frontiers in Surgery, 2023)
Branchial cleft cysts are congenital diseases of the neck caused by abnormal embryonic development of the first to fourth branchial clefts. Most branchial cleft cysts are found in the head and neck, but branchial cleft cysts arising in posterior mediastinum are rarely reported. We report a 44-year-old Chinese man who was found to have a right-posterior mediastinal mass on chest computed tomography (CT) during a physical examination. The size of the mass was about 30.6 mm*25.1 mm and enhanced CT of the chest showed an occupying lesion in the right parietal esophagus of the upper-posterior mediastinum with no significant enhancement. The patient was considered to have a neurogenic tumor with cystic change and underwent posterior mediastinal tumor resection. Postoperatively, pathological examination confirmed the final diagnosis of bronchial cleft cyst. The patient was discharged on the 7th day after surgery. One year postsurgery, no obvious recurrence was found in reexamination.